Moving Upstream and Going Local: The Responsibility to Protect Ten Years Later - Moix, Bridget (2015)
Ten years ago the international community pledged to protect civilians from genocide, ethnic cleansing, war crimes, and crimes against humanity by endorsing the responsibility to protect (R2P) doctrine. Yet today, horrific violence against civilians continues in places like Syria, Iraq, and South Sudan. This article examines some of the progress and gaps in the international community’s efforts to better protect civilians against mass violence over the past decade. It proposes two emerging directions for advancing the R2P agenda in the coming years: 1) greater focus on upstream prevention, and 2) increased support for locally-led peacebuilding and prevention actors and capacities.